Use of antimicrobials in pediatric wards of five Brazilian hospitals - Thais de Barros Fernandes; Sheila Feitosa Ramos; Luísa Rodrigues Furtado Leitzke; Ronaldo Gomes Alexandre Júnior; Janaína Morais de Araújo; Alcidésio Sales de Souza Júnior; Alice Ramos Oliveira da Silva; Isabela Heineck; Marta Maria de França Fonteles; Louise E. Bracken; Matthew Peak; Divaldo Pereira de Lyra Junior; et al. (BMC, 2024)
Abstract The use of antimicrobials (AMs) in pediatric infections is common practice and use may be inappropriate leading to antimicrobial resistance. Off-label AM use is also common in this group and can result in drug-related problems. There is lack of DUR data in Brazil and in Latin America, specially for AM pediatric use. The aim of this study was to describe the utilization of AMs in hospitalized children in five hospitals in Brazil. We conducted an observational study of the utilization of AMs in pediatric wards in hospitals in the states of Ceará (CE), Sergipe (SE), Rio de Janeiro (RJ), Rio Grande do Sul (RS) and the Federal District (DF). Data derived from patient medical records and prescriptions were collected over a six-month period in each hospital. The number of AMs used by each patient was recorded, and AM use was assessed using Days of therapy (DOT) and Length of therapy (LOT) per 1000 patient days according to different patient characteristics. Off-label (OL) use was described according to age. The study analyzed data from 1020 patients. The sex and age distributions were similar across the five hospitals. However, differences were found for comorbidities, history of ICU admission and length of hospital stay. The most common diseases were respiratory tract infections. There were wide variations in DOT/1000PD (278-517) and LOT/1000PD (265-390). AM utilization was highest in the hospital in SE. The consumption of second-generation penicillins and cephalosporins was high. The prevalence of OL use of AMs was higher for patients in the RJ hospital, in infants, in patients who underwent prolonged hospital stays, and in patients who used multiple AMs. The AM that showed the highest prevalence of OL use was azithromycin, in both oral and parenteral formulations. Overall AM use was high and showed differences in each setting, possibly influenced by local characteristics and by prescribing standards adopted by pediatricians.